Is Parkinson's Disease Associated with Increased Mortality, Poorer Outcomes Scores, and Revision Risk After THA? Findings from the Swedish Hip Arthroplasty Register. Issue 6 (June 2019) - Wojtowicz, Alex Leigh; Mohaddes, Maziar; Odin, Daniel; Bülow, Erik; Nemes, Szilard; Cnudde, Peter
Abstract: Background: Neurological conditions such as Parkinson's disease are commonly accepted as a risk factor for an increased likelihood of undergoing revision surgery or death after THA. However, the available evidence for an association between Parkinson's disease and serious complications or poorer patient-reported outcomes after THA is limited and contradictory. Questions/purposes: (1) Do patients with a preoperative diagnosis of Parkinson's disease have an increased risk of death after elective THA compared with a matched control group of patients? (2) After matching for patient- and surgery-related factors, do revision rates differ between the patients with Parkinson's disease and the matched control group? (3) Are there any differences in patient-reported outcome measures for patients with Parkinson's disease compared with the matched control group? Methods: Data were derived from a merged database with information from the Swedish Hip Arthroplasty Register and administrative health databases. We identified all patients with Parkinson's disease who underwent THA for primary osteoarthritis between January 1, 1999 and December 31, 2012 (n = 490 after exclusion criteria applied). A control group was generated through exact one-to-one matching for age, sex, Charlson comorbidity index, surgical approach, and fixation method. Risk of death and revision were compared between the groups using Kaplan-Meier and log-rank testing. Patient-reported outcome measures (PROMs), routinely recorded as EQ-5D, EQ VAS, and pain VAS, were measured at the preoperative visit and at 1-year postoperatively; mean absolute values for PROM scores and change in scores over time were compared between the two groups. Results: The risk of death did not differ at 90 days (control group risk = 0.61%; 95% CI = 0.00–1.3; Parkinson's disease group risk = 0.62%; 95% CI = 0.00–1.31; p = 0.998) or 1 year (control group = 2.11%; 95% CI = 0.81–3.39; Parkinson's disease group = 2.56%, 95% CI = 1.12–3.97; p = 0.670). At 9 years, the risk of death was increased for patients with Parkinson's disease (control group = 28.05%; 95% CI = 22.29–33.38; Parkinson's disease group = 54.35%; 95% CI = 46.72–60.88; p < 0.001). The risk of revision did not differ at 90 days (control group = 0.41%; 95% CI = 0.00–0.98; Parkinson's disease group = 1.03%; 95% CI = 0.13–1.92; p = 0.256). At 1 year, the risk of revision was higher for patients with Parkinson's disease (control group = 0.41%; 95% CI = 0.00–0.98; Parkinson's disease group = 2.10%; 95% CIs = 0.80–3.38; p = 0.021). This difference was more pronounced at 9 years (control group = 1.75%; 95% CI = 0.11–3.36; Parkinson's disease group = 5.44%; 95% CI = 2.89–7.91; p = 0.001) when using the Kaplan-Meier method. There was no difference between the control and Parkinson's disease groups for level of pain relief at 1 year postoperatively (mean reduction in pain VAS score for control group = 48.85, SD = 20.46; Parkinson's disease group = 47.18, SD = 23.96; p = 0.510). Mean change in scores for quality of life and overall health from preoperative measures to 1 year postoperatively were smaller for patients in the Parkinson's disease group compared with controls (mean change in EQ-5D scores for control group = 0.42, SD = 0.32; Parkinson's disease group = 0.30, SD = 0.37; p 0.003; mean change in EQ VAS scores for control group = 20.94, SD = 23.63; Parkinson's disease = 15.04, SD = 23.00; p = 0.027). Conclusions: Parkinson's disease is associated with an increased revision risk but not with short-term mortality rates relevant to assessing risk versus benefit before undergoing THR. The traditional reluctance to perform THR in patients with Parkinson's disease may be too conservative given that the higher long-term risk of death is more likely due to the progressive neurological disorder and not THR itself, and patients with Parkinson's disease report comparable outcomes to controls. Further research on outcomes in THR for patients with other neurological conditions is needed to better address the broader assumptions underlying this traditional teaching. Level of Evidence Level III, therapeutic study.